2021
DOI: 10.3390/app11083684
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Dispersive X-ray Spectroscopic Investigation of Failed Dental Implants Associated with Odontogenic Maxillary Sinusitis

Abstract: The failed dental implant associated with maxillary sinusitis is a multifactorial phenomenon and should be investigated thoroughly. The inflammatory process induced by accumulated biofilm and wear debris may increase mucous secretion and mucous thickening, which finally may lead to severe complications such as maxillary sinusitis. The inflammatory cytokines might compromise the long-term osseointegration of the related implant. In this study, implants retrieved from three patients who experienced implant failu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In a previous study of chronic sinusitis-related implant failure in the late phase, we observed that contamination of potentially toxic elements, microorganism infection, and long perforation of the implant apex into the sinus might play a central role in dental implant failure associated with maxillary sinusitis [26]. In the current cases, on the SEM images, there was no detection of bacteria or other infectious organisms on the surface of all three implants, which suggested a low possibility of a bacterial infection etiology.…”
Section: Discussionmentioning
confidence: 97%
“…In a previous study of chronic sinusitis-related implant failure in the late phase, we observed that contamination of potentially toxic elements, microorganism infection, and long perforation of the implant apex into the sinus might play a central role in dental implant failure associated with maxillary sinusitis [26]. In the current cases, on the SEM images, there was no detection of bacteria or other infectious organisms on the surface of all three implants, which suggested a low possibility of a bacterial infection etiology.…”
Section: Discussionmentioning
confidence: 97%
“…Several causes may contribute to implant failure. In a prior investigation into the late stages of chronic sinusitis-related implant failure, it was found that long implant apex perforation into the sinus, microbe infection, and contamination of potentially toxic elements may be major factors in dental implant failure linked to maxillary sinusitis [ 21 , 22 ]. According to Kim et al case report, who performed lateral sinus irrigation on two patients with maxillary sinusitis after implant surgery, it was observed that all opaque images on cone beam CT decreased significantly 2 weeks after sinus irrigation [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of the long-term corrosion not only leads to the release of ions into the peri-implant tissue but also a disintegration of the implant that contributes to material fatigue and even fracture of the abutments, implant body, or both. From our recent study [ 15 , 16 ], Ti, C, and O from EDS analysis are not harmful elements due to the chemical composition of the implant. However, inorganic impurities such as Al, zinc (Zn), Si, and magnesium (Mg), with other elements such as nitrogen (N), F, P, Cl, and Na contribute to the corrosion process.…”
Section: Discussionmentioning
confidence: 99%
“…Cells undergoing degeneration and cell death with lipid formation were observed prevent excessive bone resorption in osteoporosis and cancer metastasis, is known as a drug that induces osteonecrosis, which may cause implant failure after tooth extraction in the jaw [12,13]. According to the AAOMS, BRONJ is defined as follows: (1) present or a history of treatment with antiresorptive or antiangiogenic agents, (2) exposed bone or bone that can be probed through an intraoral or extraoral fistula in the maxillofacial region that has persisted for more than 8 weeks, and (3) no history of radiation therapy to the jaws or obvious metastatic disease to the jaws [11,[14][15][16].…”
Section: Discussionmentioning
confidence: 99%